Virtual customer service: building your chatbot - Sousa, David N. (2019)
Nowadays, there is a significant evolution in the simulation of conversations with humans through chats. These chatbots provide an improvement in organizational efficiency and enhance the performance in supporting customers and partners. That is why they are increasingly a trend on the web. There are several solutions to conversational virtual agents and chatbots at this time. Many of these solutions have built-in artificial intelligence, natural language processing, and understanding systems. This research aims to build a roadmap for those who want to develop a virtual assistant using a framework or a pre-built solution. This work compares the several products related to chatbots providing information that helps one to find the best solution for each case.